Pseudomonas aeruginosa Exopolyphosphatase Is Also a Polyphosphate: ADP Phosphotransferase. (21st October 2015) - Beassoni, Paola R.; Gallarato, Lucas A.; Boetsch, Cristhian; Garrido, Mónica N.; Lisa, Angela T.
Abstract : Pseudomonas aeruginosa exopolyphosphatase ( pa Ppx; EC 3.6.1.11) catalyzes the hydrolysis of polyphosphates (polyP), producing polyPn−1 plus inorganic phosphate( P i ) . In a recent work we have shown that pa Ppx is involved in the pathogenesis of P. aeruginosa . The present study was aimed at performing the biochemical characterization of this enzyme. We found some properties that were already described for E. coli Ppx ( ec Ppx) but we also discovered new and original characteristics of pa Ppx: (i) the peptide that connects subdomains II and III is essential for enzyme activity; (ii)N H 4 + is an activator of the enzyme and may function at concentrations lower than those of K + ; (iii) Zn 2+ is also an activator of pa Ppx and may substitute Mg 2+ in the catalytic site; and (iv) pa Ppx also has phosphotransferase activity, dependent on Mg 2+ and capable of producing ATP regardless of the presence or absence of K + orN H 4 + ions. In addition, we detected that the active site responsible for the phosphatase activity is also responsible for the phosphotransferase activity. Through the combination of molecular modeling and docking techniques, we propose a model of the pa Ppx N-terminal domain in complex with a polyP chain of 7 residues long and a molecule of ADP to explain the phosphotransferase activity.